JUMPA Vol.2 No.3 Okt 2015 ANALISIS PENGARUH FIXED ASSET RATIO (FAR), LIKUIDITAS (CR), RETAINED EARNING (RE), RETURN ON ASSET (ROA) TERHADAP STRUKTUR MODAL: ANALISIS PENGARUH FIXED ASSET RATIO (FAR), LIKUIDITAS (CR), RETAINED EARNING (RE), RETURN ON ASSET (ROA) TERHADAP STRUKTUR MODAL - Fangky A. Sorongan Perbanas Institute (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
This research is performed in order to test the influence of variable, Fixed Asset Ratio (FAR), Likuiditas (CR), Retained Earning (RE) and Return On Asset (ROA), on Debt to Equity Ratio (DER), comparation company in the BEI LQ 45 during period 2011-2014. Methodology research as the sample used purposive sampling with criteria as (1). The Company listed to the BEI LQ45 during research period (2011- 2014); (2). The Company always showed financial report during research period (2011-2014); (3). Having complete data which suitable for the research. The data based on publicity ICMD since 2011-2014. Analysis technic with multilinier regression of polled data and hypotheses test used t-statisic and f-statistic at level of significance 5%. Results of analysis showed that the predictive ability of the four independent variables (FAR, CR, RE, ROA) is 55.2% and it shown by adjusted R2value. Based on the test statistic F indicates that the variables FAR, CR, RE ROA simultantly affect DER on companies listed in Indonesia Stock Exchange for the period 2011-2014 because has a significance value less than 5% of Alpha value. Meanwhile, based on statistical t test showed that the ROA and RE is negative and significant impact of DER because it has a significance value less than 5% of Alpha value.